Trade Hedging and the Dynamic Stability of the Foreign Exchange Market - Witte, Willard E. (Quarterly Journal of Economics, 1980)
This paper uses a simple difference equation model to investigate the dynamic characteristics of the foreign exchange market under a regime of flexible exchange rates. It is shown that unhedged trade transactions can produce a dynamically unstable market, particularly if contracts are denominated in the seller's currency. We then examine the influence of trade hedging, using either the forward market or an artificial currency unit, and find that it considerably enhances the overall likelihood of stability.